Left Subclavian Transcatheter Aortic Valve Replacement Under Combined Interscalene and Pectoralis Nerve Blocks: A Case Series. Issue 12 (15th December 2018) - Block, Michael; Pitchon, Darsi N.; Schwenk, Eric S.; Ruggiero, Nicholas; Entwistle, John; Goldhammer, Jordan E.
Abstract : The treatment for aortic stenosis is evolving rapidly with new developments in transcatheter aortic valve replacement (TAVR). While the procedure was initially performed under general anesthesia with invasive monitoring and transesophageal echocardiography, recent trends have shifted toward less invasive strategies. Transfemoral TAVRs are frequently performed under sedation; however, TAVRs using alternative access sites, such as the subclavian artery, are typically performed under general anesthesia. This case series describes 3 patients who underwent subclavian TAVR under combined pectoralis and interscalene blocks. All patients tolerated the procedure without complication, requiring no airway manipulation and minimal postoperative analgesia.